UMP Library introduced Waste4Fine programme fines for late return of library books with plastic drinking bottles or canned drinks - Wan Nurulhuda, Wan Zakaria (2019)
Universiti Malaysia Pahang (UMP) Library has introduced an ingenious way as part of its efforts to support the university’s green campaign – by making students pay their fines for late return of library books with plastic drinking bottles and canned drinks.